MECHANISM OF ACTION, EFFICACY, AND SAFETY OF PROPOLIS FOR THE MANAGEMENT OF ORAL MUCOSITIS: A SYSTEMATIC REVIEW - RAMDHIANI, ANIS NUR; HIDAYAT, WAHYU; WAHYUNI, INDAH SUASANI (International Journal of Applied Pharmaceutics, 2022)
Oral mucositis (OM) is an oral mucosal inflammation and complication of chemotherapy and/or radiotherapy. One of the natural agents that has been widely studied as an alternative therapy for OM was Propolis. This review aims to analyze the effectiveness and safety of propolis and its mechanism of action in preventing and treating OM through clinical study in human and animal models. Articles searched using the keywords “Oral Mucositis” AND “Propolis”, conducted through PubMed, ScienceDirect, and Cochrane Library databases. The inclusion criteria were: Clinical Trial and Animal Study design; in English; full paper available; published between 2016-2021; and high range of quality and articles in line to the research topic. RoB-tools JADAD Oxford Quality Scoring System and SYRCLE’s RoB tool was used for risk of bias determination. This paper writing refers to PRISMA guidelines. In vivo studies and clinical trials have shown that propolis can reduce OM Index scores in animals or OM grades in patients. Propolis can also reduce the symptoms of inflammation in OM and almost all articles stated that there were no side effects of propolis for oral mucositis. In vivo studies showed that propolis was able to inhibit pro-inflammatory markers, hypoxia markers, MPO serum levels, and TNF-alpha cytokines, but increased the expression of pS6, pAKT, NF-B, and GSH. Propolis is effective and safe to use in patients receiving chemotherapy/radiotherapy to prevent the severity and potential for OM therapy. The mechanism of action of propolis in overcoming clinical symptoms of OM is as an anti-inflammatory, antioxidant, and helps accelerate wound healing.